RANCANG BANGUN FITUR APLIKASI UNTUK MENENTUKAN KLASIFIKASI KUALITAS AIR DENGAN MENGGUNAKANMETODE STORET - Irenda Talitha Salsabila; Tata Sutabri (CV. ADIBA AISHA AMIRA, 2023)
This study aims to design application features that determine water quality qualifications using the STORET method. This is intended so that classification checking can be carried out with time efficiency and action effectiveness while still paying attention to the accuracy of the classification. This research itself is a type of literature study research with the preparation of research results using several previous references as an initial part of the design. The design in this study is basically still tentative and still needs to be studied in more depth as well as being tested to see how effective the built application features are in an effort to detect water quality qualifications. Basically this design is intended to save time checking water quality while prioritizing the accuracy of the determination. In addition, the integration of the Internet of Things through the application feature for determining water quality classification is also a form of innovation that is really highly anticipated in today's all-mobile era.